Correlations between the ECD spectra and absolute configuration of bridged-ring lactones: revisiting Beecham's rule. Issue 42 (15th October 2021) - Zhang, Jun-Yao; Yang, Bei-Bei; Yang, Ya-Dong; Gao, Fan; Liu, Wen-Qiang; Li, Li
Abstract : We present the theoretical verification, revision and enrichment of Beecham's rule for bridged-ring lactones. This provides an alternative way to correlate experimental ECD data with stereochemistry in addition to quantum-chemical calculation. Abstract : Bridged lactones frequently appear as structural fragments in natural products. To elucidate their stereochemistry using electronic circular dichroism (ECD) spectra, Beecham correlated the sign of the Cotton effect (CE) from the n → π* transition of lactones at approximately 220 nm with the skeleton of bridged lactones. By combining experimental and theoretical ECD analyses of various bridged lactones using time-dependent density functional theory calculations and a methodology for extracting core structures, Beecham's rule was revisited and revised to define the scope of application. Both the position of the β-C atom in the larger lactone system and the additive contribution of groups at β-C exerted effects on the sign of the CE. The revised rule provides an alternative way to interpret experimental ECD data in addition to quantum-chemical calculation for various bridged lactones.